THE AMERICAN ENGLISH ACCENT: PHONOLOGICAL ANALYSIS - Ambalegin, Ambalegin; Afriana, Afriana; Handayani, Nurma Dhona (IdeBahasa, 2024)
This research aims at identifying the American English accents produced by the Americans. The American phonation was taken from Thomas’ book, An Introduction to the Phonetics of American English. This qualitative research took the data from the English speeches spoken by the famous Americans on YouTube. This research applied the observational method to collect the data, and a phonological approach, identity method, and articulatory phonetic identification to analyze the data. It is identified that the Americans have true [t], flap [t]. held [t], and vanishing [t]. The dark [l] and the light [l] are also articulated. The Americans pronounce the bunched [ɹ] and R-colored vowels, and they drop the final [r]. The article a is pronounced as /e/, /ɒ/ is pronounced as /ɑ:/, and /ɑ:/ is pronounced as /æ/. The letter <o> is pronounced as [oʊ].